광물탄산화 공정 이후 발생하는 잔사슬래그의 수계 내 비소 제거 기작 - 김경태; 일함 압둘 라티에프; 김단우; 김선희; 이민희 (자원환경지질, 2022)
Laboratory-scale experiments were performed to identify the As removal mechanism of the residual slag generated after the mineral carbonation process. The residual slags were manufactured from the steelmaking slag (blast oxygen furnace slag: BOF) through direct and indirect carbonation process. RDBOF (residual BOF after the direct carbonation) and RIBOF (residual BOF after the indirect carbonation) showed different physicochemical-structural characteristics compared with raw BOF such as chemical-mineralogical properties, the pH level of leachate and forming micropores on the surface of the slag. In batch experiment, 0.1 g of residual slag was added to 10 mL of As-solution (initial concentration: 203.6 mg/L) titrated at various pH levels. The RDBOF showed 99.3% of As removal efficiency at initial pH 1, while it sharply decreased with the increase of initial pH. As the initial pH of solution decreased, the dissolution of carbonate minerals covering the surface was accelerated, increasing the exposed area of Fe-oxide and promoting the adsorption of As-oxyanions on the RDBOF surface. Whereas, the As removal efficiency of RIBOF increased with the increase of initial pH levels, and it reached up to 70% at initial pH 10. Considering the PZC (point of zero charge) of the RIBOF (pH 4.5), it was hardly expected that the electrical adsorption of As-oxyanion on surface of the RIBOF at initial pH of 4-10. Nevertheless it was observed that As-oxyanion was linked to the Fe-oxide on the RIBOF surface by the cation bridge effect of divalent cations such as Ca2+, Mn2+, and Fe2+. The surface of RIBOF became stronger negatively charged, the cation bridge effect was more strictly enforced, and more As can be fixed on the RIBOF surface. However, the Ca-products start to precipitate on the surface at pH 10-11 or higher and they even prevent the surface adsorption of As-oxyanion by Fe-oxide. The TCLP test was performed to evaluate the stability of As fixed on the surface of the residual slag after the batch experiment. Results supported that RDBOF and RIBOF firmly fixed As over the wide pH levels, by considering their As desorption rate of less than 2%. From the results of this study, it was proved that both residual slags can be used as an eco-friendly and low-cost As remover with high As removal efficiency and high stability and they also overcome the pH increase in solution, which is the disadvantage of existing steelmaking slag as an As remover. 제강슬래그를 이용한 광물탄산화 공정 이후 발생하는 잔사슬래그의 비소(As) 제거 기작 규명을 위해, 전로제강슬래그(blast oxygen furnace slag: BOF)에 직접 및 간접탄산화 공정이 각각 적용된 두 종류의 잔사슬래그를 대상으로 실험실 규모의 실험을 실시하였다. 광물탄산화 공정은 잔사슬래그의 화학적-광물학적 조성변화, 용출수의 pH 저감, 표면 미세공극 형성 등 기존 제강슬래그의 특성을 변화시키는 것으로 밝혀졌다. 다양한 pH 범위의 As 인공오염수(초기농도: 203.6 mg/L)에 잔사슬래그를 반응시킨 배치실험에서, RDBOF (직접탄산화 후 BOF)는 초기 pH가 감소할수록 As 제거효율이 증가하는 경향을 보이며 초기 pH가 1인 환경에서 99.3%의 As 제거효율을 나타냈다. 이는 RDBOF 표면을 피복하던 CaCO3가 낮은 초기 pH 환경에서 용해되어 RDBOF 표면에서 철산화물의 노출 면적을 증가시킴으로 인해, 철산화물의 As 음이온 표면 흡착을 촉진한 것에서 기인한 것으로 판단되었다. 반면 RIBOF (간접탄산화 후 BOF)는 초기 pH가 높은 환경일수록 As 제거효율이 증가하며 초기 pH 10의 As 오염수에서 70.0%의 가장 높은 As 제거효율을 보였다. RIBOF의 영전하점(pH 4.5)을 고려할 때, 초기 pH 4-10 조건에서 음전하를 띠는 RIBOF의 표면에 As 음이온의 전기적 인력에 의한 표면 흡착은 발생하기 어려울 것으로 예상되었다. 다만 수용액 내 용존하는 Ca2+, Mn2+, Fe2+와 같은 2가 양이온들에 의해 As 음이온이 RIBOF 내 철산화물에 간접적으로 고정되는 양이온 가교효과(cation bridge effect)가 발생하였고, 초기 pH가 높은 환경일수록 슬래그 표면이 더 강한 음전하를 띠며 양이온 가교효과가 가속화되어, 결과적으로 많은 As가 흡착된 것으로 판단되었다. 하지만 강알칼리 (pH 10-11 이상) 조건에서는 RIBOF 표면에 생성된 칼슘침전물이 철산화물을 피복함으로써 철산화물에 의한 As 음이온 표면 흡착을 저해하는 현상이 발생하였다. 또한 배치실험 이후 회수된 잔사슬래그에 TCLP 시험을 수행한 결과, RDBOF와 RIBOF 모두 2% 미만의 As 탈착률을 보여 안정적인 형태로 As가 고정되어 있음이 확인되었다. 본 연구 결과를 통해, 잔사슬래그가 기존에 As 제거제로 활용되던 제강슬래그의 단점인 수계의 급격한 pH 상승을 억제하는 동시에, 높은 As 제거효율 및 안정성을 나타내는 저비용-친환경의 As 제거제로서의 활용 가능성을 입증하였다.